Bee diversity in secondary forests and coffee plantations in a transition between foothills and highlands in the Guatemalan Pacific Coast - Armas-Quiñonez,Gabriela; Ayala-Barajas,Ricardo; Avendaño-Mendoza,Carlos; Lindig-Cisneros,Roberto; del-Val,Ek (PeerJ, 2020)
Background Although conservation of pristine habitats is recognized in many countries as crucial for maintaining pollinator diversity, the contribution of secondary forest conservation is poorly recognized in the Latin American context, such as in Guatemala. San Lucas Tolimán (SLT) is a high-quality coffee production region from the Atitlan Province, which has the second highest deciduous forest cover in Guatemala and pristine forest is prioritized for conservation. In contrast, secondary forest protection is undetermined, since these forests are normally removed or strongly affected by coffee farming practices. This situation may affect the diversity of native pollinators, mainly bees, which usually rely on the secondary forest for food resources. Methods We conducted a study to investigate the importance of secondary forests around the SLT coffee plantations (Coffea arabica L.) for pollinators. We compared bee diversity (richness, abundance and composition) in secondary forests of different age and coffee plantations with diverse farming techniques. Being the first study of pollinators in Guatemalan coffee plantations, we also recorded data for an entire year (2013–2014) in order to describe bee seasonality. Results We found significant differences in bee diversity between the coffee plantations and secondary forests, particularly early secondary forests showed higher bee abundances but diversity indices were similar between different vegetation type plots. In the early dry season, secondary forests showed the greatest native bee diversity. During the late dry season, when the coffee was flowering, honey bees were dominant in the same plots. This study provides important management insights to support the conservation of pollinators, since our results offer guidelines to improve coffee production by increasing native pollinator diversity.
Keywords: Pollination; Native bee; Megachillidae; Secondary forest; Apis mellifera; Insect conservation; Guatemala; Insect diversity; Coffee